2011
DOI: 10.1016/j.pbb.2011.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic-like effects of inhaled linalool oxide in experimental mouse anxiety models

Abstract: Linalool oxide is a monoterpene that is found in some species of aromatic plants. The effects of the inhalation of linalool oxide (0.65%, 1.25%, 2.5% and 5.0% w/w) in the elevated plus-maze and light/dark box tests as animal models of anxiety were investigated in adult male mice and compared with the effects of the reference anxiolytic diazepam (0.5 and 2.0 mg/kg), administered intraperitoneally. Additionally, the effects of inhaled linalool oxide were investigated in the rotarod test. Linalool oxide significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 39 publications
4
54
0
5
Order By: Relevance
“…In our study, the Rosa canina extract noticeably decreased the level of anxiety in rats. It should be mentioned that linalool inhalation was also shown to reduce anxiety [33]. As was reported, linalool prevents glutamate (i.e., the main excitatory neurotransmitter) from binding to its receptors in the rat neocortex [34].…”
Section: Discussionmentioning
confidence: 84%
“…In our study, the Rosa canina extract noticeably decreased the level of anxiety in rats. It should be mentioned that linalool inhalation was also shown to reduce anxiety [33]. As was reported, linalool prevents glutamate (i.e., the main excitatory neurotransmitter) from binding to its receptors in the rat neocortex [34].…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, OB extract decreased the level of anxiety in animals. In connection to this finding, an effect of linalool inhalation has been shown to reduce anxiety (58). Also, it has been reported that linalool prevents glutamate (the main excitatory neurotransmitter) from binding to its receptors in the neocortex of rats (59).…”
Section: Discussionmentioning
confidence: 88%
“…Despite the availability of treatment with several anxiolytic drugs currently on the market, many of these pharmaceutical options, such as benzodiazepines, are fairly nonselective and may cause significant adverse effects such as dependence, tolerance, withdrawal syndrome or muscle relaxation (Souto-Maior et al, 2011).…”
Section: Discussionmentioning
confidence: 99%